2023
DOI: 10.3390/su151310123
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Women’s Green Entrepreneurial Intention on Green Entrepreneurial Behavior through University and Social Support

Abstract: Green entrepreneurship has an extensive role in solving environmental issues and contributes significantly to friendly environmental practices. In this study, we examined the effect of green entrepreneurial intention on green entrepreneurial behavior through the mediating influence of university entrepreneurial support and moderating the role of social support. The nature of this study was cross-sectional, and data were gathered from a sample of 438 women university students. Partial least squares structural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
(178 reference statements)
0
5
0
Order By: Relevance
“…All the countries are struggling to promote green development to solve these challenges. As organizations are the basic unit of economic development, their productive and operational activities impact the natural environment [2]. Organizations should pay more devotion to environmental and social challenges, integrate low-carbon objectives into their long-term strategic decisions, and fulfill their social responsibilities to minimize their carbon emissions [3].…”
Section: Introductionmentioning
confidence: 99%
“…All the countries are struggling to promote green development to solve these challenges. As organizations are the basic unit of economic development, their productive and operational activities impact the natural environment [2]. Organizations should pay more devotion to environmental and social challenges, integrate low-carbon objectives into their long-term strategic decisions, and fulfill their social responsibilities to minimize their carbon emissions [3].…”
Section: Introductionmentioning
confidence: 99%
“…This relationship has support from prior studies. The study by Li et al (2023) established the student's entrepreneurial intention is related to their entrepreneurial behavior. Furthermore, Mathews et al (2021) demonstrated that entrepreneurial intention strongly predicts entrepreneurial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship has support from prior studies. The study by Li et al . (2023) established the student’s entrepreneurial intention is related to their entrepreneurial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence supports this notion, with several studies demonstrating that entrepreneurial intention has a significant and positive impact on entrepreneurial activities (Belchior & Lyons, 2021;L. Cai et al, 2021;Duong et al, 2022;Farooq, 2018;Li et al, 2023;Yaseen et al, 2018;Yi, 2021). However, contradictory findings suggest no significant influence of entrepreneurial intention on entrepreneurial activities (Yang et al, 2022).…”
Section: The Effect Of Entrepreneurial Intention On Entrepreneurial A...mentioning
confidence: 98%
“…Several studies have addressed the crucial question of whether entrepreneurial intention can serve as a robust predictor of actual entrepreneurial activity (Belchior & Lyons, 2021;L. Cai et al, 2021;Duong et al, 2022;Farooq, 2018;Jin, 2017;Li et al, 2023;Yang et al, 2022;Yaseen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%